Biological efficiency indicators and competitive ability in intercropped systems of xerophilous forage plants: a review (Research, Society and Development, 2022)
In arid and semi-arid regions, it is essential to search for strategies that favor the cultivation of forage plants, such as the use of forage species that are resistant or tolerant to local climatic conditions, as well as the use of management practices, such as intercropping, due to livestock is the main economic activity developed in these regions. The consortium promotes an increase in the productivity of plants cultivated by area, however, when intercropped, there is interspecific competition between the cultures, reducing the individual yield of the plants. In this sense, this review aimed to explain concepts and applicability of indicators of biological efficiency and competitive ability of consortia of xerophilous forage plants, to improve the efficiency and management of these systems. To carry out this review, searches were carried out in the following databases: Google Scholar, CAPES Periodicals, SciELO and Scopus. The cultivation of xerophilous forage plants is an alternative to guarantee the supply of quality and quantity food for animals in arid and semi-arid environments throughout the year, especially in the dry season. The application of biological indices and competitive ability in intercropped systems helps to understand the interspecific relationships between intercropped crops, as well as the economic benefits and essential aspects of cultivation.